Blockade of VEGFR-1 and VEGFR-2 Enhances Paclitaxel Sensitivity in Gastric Cancer Cells - Hwang, Jun-Eul (Yonsei University College of Medicine, 2013)
PURPOSE: Hypoxia-inducible factor-1α (HIF-1α) increases transcription of the vascular endothelial growth factor (VEGF) gene. Inhibition of VEGF abolishes VEGF mediated induction of HIF-1α. Recent reports suggested that HIF-1α also mediated the induction of class III β-tubulin (TUBB3) in hypoxia. TUBB3 confers resistance to taxanes. Inhibition of VEGF may decrease the expression of HIF-1α and TUBB3. This study was undertaken to investigate the roles of vascular endothelial growth factor receptor (VEGFR) in gastric cancer cell behavior and to identify methods to overcome paclitaxel resistance in vitro. MATERIALS AND METHODS: The protein expression levels of HIF-1α and TUBB3 were measured in human gastric cancer cell lines (AGS) under normoxic and hypoxic conditions. The relationship between TUBB3 and paclitaxel resistance was assessed with small interfering TUBB3 RNA. AGS cells were treated with anti-VEGFR-1, anti-VEGFR-2, placental growth factor (PlGF), bevacizuamb, and paclitaxel. RESULTS: Hypoxia induced paclitaxel resistance was decreased by knockdown of TUBB3. Induction of HIF-1α and TUBB3 in AGS is VEGFR-1 mediated and PlGF dependent. Hypoxia-dependent upregulation of HIF-1α and TUBB3 was reduced in response to paclitaxel treatment. Expressions of HIF-1α and TUBB3 were most decreased when AGS cells were treated with a combination of paclitaxel and anti-VEGFR-1. AGS cell cytotoxicity was most increased in response to paclitaxel, anti-VEGFR-1, and anti-VEGFR-2. CONCLUSION: We suggest that blockade of VEGFR-1 and VEGFR-2 enhances paclitaxel sensitivity in TUBB3-expressing gastric cancer cells.